The Influence Of Integrity, Commitment And Work Ethic On Performance Of Disaster Management Agency Employees Majene District Region - Rakhman, Basri; Said, Muh; Gaus, Rusdia (Pascasarjana STIE Amkop Makassar, 2024)
This research uses quantitative methods. The research was carried out at the Majene Regency Regional Disaster Management Agency office. This research distributed questionnaires to 57 respondents. The method used is a quantitative method by testing hypotheses, namely Validity Test, Reliability Test, Classical Assumption Test, Multiple Regression Analysis, T Test, F Test, and Coefficient of Determination.The results of the research show that integrity has a positive and significant effect on the performance of employees of the Majene Regency Regional Disaster Management Agency. In the second variable, commitment has no effect on the performance of the Majene Regency Regional Disaster Management Agency. In the third variable, work ethic has a positive and significant effect on employees of the Majene Regency Regional Disaster Management Agency.In the simultaneous test, namely the variables Integrity, commitment and work ethic, have a positive and significant effect on the performance of employees of the Majene Regency Regional Disaster Management Agencywhile the Determination test contributed 65.3% to employee performance, while the rest was influenced by other variables not included in the research.Keywords: Integrity, commitment, work ethic, and employee performance.